Preparation, Purification and Performance Evaluation of Polyclonal Antibody Against SARS-CoV-2 Produced in Rat - Fatemeh Yaghoobizadeh; Mohammad Roayaei Ardakani; Mohammad Mehdi Ranjbar; Mohammad Khosravi; Hamid Galehdari (Tabriz University of Medical Sciences, 2023)
Purpose: Among all known human coronaviruses, some viruses (e.g., SARS-CoV-2) cause severe pneumonia or even death. With the regard to its spread and the importance of its rapid identification/treatment, and because pAbs are relatively cheap, able to bind to more sites on antigens and even neutralize them, this study was done for the production and purification of anti-SARS-CoV-2 polyclonal antibodies (pAb) in rats. Methods: Viral antigen purification was performed by PEG/NaCl precipitation. The efficiency of the sucrose cushion method was also investigated to produce a purer antigen. Immunization was done and antibody purification was performed by ammonium sulfate precipitation (33%), dialysis, and ion-exchange chromatography. Western blotting and enzyme-linked immunosorbent assay (ELISA) were performed to verify the antibody specificity. All data were analyzed by SPSS software. Results: The results showed that the amount of concentrated virus increased with the increase of PEG concentration. Moreover, the sucrose cushion method increased its purity. Besides, induction of immune response in rats for pAb production with high titers was reached via these antigens and ELISA/western blot results indicated a suitable antibody-antigen interaction. Additionally, it was shown that ion-exchange chromatography could be a suitable technique for IgG purification. Conclusion: Herein, we presented a simple and cheap method for the purification of whole viral particles with relatively high quality. The results verified that these antigens could elicit a good immune response in the rat. The obtained pAbs showed a good specificity toward SARS-CoV-2 antigens. Accordingly, this study proposes a promising method for viral vaccine development.